(3E)-3-[(4-butylphenyl)imino]-1,3-dihydro-2H-indol-2-one - Akkurt, M; Öztürk, S; Erçag, A; Özgür, MÜ; Heinemann, FW (INT UNION CRYSTALLOGRAPHY, 2003)
The title compound, C18H18N2O, has a non-planar conformation. The indol and butylphenyl groups are connected by a C-N bond [1.433 (3) Angstrom]. The crystal structure is stabilized by intermolecular N-H...N and C-H...O interactions.
Keywords: MANNICH-BASES; ISATIN; ANTIBACTERIAL; DERIVATIVES; ANTIFUNGAL; Crystallography